The Origin of Several Pyroclastic Plateaux in the Padang Highlands (Central Sumatra) (Preliminary Paper) - M.T. Zen (Journal of Mathematical and Fundamental Sciences, 1972)
Abstract. Several pyroclastic plateaux are known in the Padang Highlands. Westerveld (1952) suggested that those rhyolitic volcanics are sheetlike deposits of paroxysmal fissure eruption similar to the incandescent clouds of the Katmai type. Field observation, however, suggested that at least the pyroclastic plateau of Bukit Tinggi might as well be the result of an air borne tuff deposition which originated from a gigantic outburst of the Manindjau volcano prior to its caldera formation. The tuff plateau of Bukit Tinggi, as revealed by the exposures in Ngarai SiAnok, is neither layered nor welded and could not be deposited in water either. The landscape between Matur and Bukit Tinggi gives the impression as if ducoed by tuff from the air.  Ringkasan. Beberapa daratan jang terbentuk dari bahan pyroklastik dikenal di Daratan Tinggi Padang. Menurut Westerveld (1952) dataran2 tinggi tersebut jang terdiri dari batuan volkanik bersifat rhyolitik merupakan endapan pyroklastik terdiri dari lembaran2 (sheetlike) dan dihasilkan oleh suatu erupsi rekahan jang sama sifatnja dengan endapan awan panas dari Gunung Katmai di Alaska. Penelitian lapangan, sebaliknja, lebih menundjukkan bahwa dataran2 tinggi tadi, terutama Dataran pyroklastik Bukit Tinggi, mungkin sekali berupa endapan pyroklastik dari udara jang dikeluarkan oleh letusan raksasa Gunung Manindjau pada saat2 mendjelang ambruknja gunung tersebut untuk membentuk kaldera Danau jang besar itu. Dataran Tinggi tufa Bukit Tinggi, sebagaimana terlihat pada singkapan2 jang djelas di Ngarai Si Anok, tidak memperlihatkan perlapisan dan djuga tidak memperlihatkan "welding". Endapan tufa tersebut djuga tidak mungkin diendapkan diair. Bentang alam antara Matur dan Bukit Tinggi memberi kesan se-akan2 di-"duco" dari udara oleh tufa.